Effect of DDAVP on Endotoxin-Induced Intravascular Coagulation in Rabbits - Paloma, M J; Páramo, J A; Rocha, E (Thrombosis and Haemostasis, 1992)
We have evaluated the effect of l-Deamino-8D-arginine vasopressin (DDAVP) on an experimental model of intravascular coagulation (DIC) induced in rabbits by injection of 20 µg kg–1 h–1 during 6 h of E. coli lipopolysaccharide. DDAVP significantly ameliorated the platelet drop and fibrinogen decrease (p <0.01) induced by endotoxin in control animals. A significant reduction in factor XII consumption (p <0.01) and a decrease in the generation of endotoxin induced PAI-1 activity in rabbits circulation was also observed (p <0.005). Moreover, fibrin deposition in kidneys of rabbits receiving DDAVP was significantly reduced as compared to control animals. Finally, the mortality rate in the control group was significantly higher than in DDAVP-treated rabbits (p <0.01). The hemostatic changes induced by DDAVP correlated with lower fibrin deposition and reduction in mortality rates.